Prognostic Nutritional Index Predicts Response and Prognosis in Cancer Patients Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Ni, Liwei; Huang, Jing; Ding, Jiyuan; Kou, Junyan; Shao, Tingting; Li, Jun; Gao, Liujie; Zheng, Wanzhen; Wu, Zhen (Frontiers in Nutrition, 2022)
Abstract Objective: To investigate the association between pretreatment prognostic nutritional index (PNI) and clinical survival outcomes for advanced-stage cancer patients treated with immune checkpoint inhibitors (ICIs). Methods: We conducted a comprehensive literature search to identify eligible studies concerning the relationship between pretreatment PNI and survival outcomes in advanced cancer patients treated with ICIs. Published data were extracted and pooled odds ratio (pOR) for objective response rate (ORR), disease control rate (DCR), and pooled hazard ratio (pHR) for overall survival (OS), progressive-free survival (PFS), along with 95% confidence intervals (95% CIs) were calculated. Results: Twelve studies with 1,359 participants were included in our study. A higher level of PNI indicated a greater ORR (pOR = 2.17, 95% CI = 1.52–3.10) and favorable DCR (pOR = 2.48, 95% CI = 1.87–3.29). Low PNI was associated with a shorter OS (pHR = 2.24, 95% CI = 1.57–3.20) and unfavorable PFS (pHR = 1.61, 95% CI = 1.37–1.88). Conclusion: Low PNI might be an effective biomarker of poor tumor response and adverse prognosis of advanced cancer patients with ICIs. Further studies are required to verify the significance of PNI in clinical practice.